Factors associated with the development of congenital anomalies in newborns (Research, Society and Development, 2021)
Congenital defects are pathological conditions that are determined by factors that arise concurrently with birth, during or after conception. However, anomalies can also be developed by several factors, maternal age, environmental factors, alterations in tissue development and also by infectious agents. Congenital alterations can be associated by a variety of etiological factors. The study aims to present results found in the qualitative integrative review, which present the factors associated with congenital anomalies, exposing the different ways in which these manifestations can develop. The research is an integrative literature review of the qualitative type, the preparation of a methodological survey for the research was carried out from November 4, 2021 to November 9, 2021, the database used was Medical Literature Analysis and Retrieval System Online (MEDLINE) and Scientific Electronic Library Online (SCIELO). Using the Medical Subject Headings (MeSH) and the Health Sciences Descriptors (DeCS). it is clear that there are several factors which can cause the development of congenital anomalies, considering the results, care and attention to the prenatal period is essential to carry out diagnoses and interventions in the face of anomalies, however, when will Existing after birth, the main measures for having a neonatal neuroprotective care are sleep protection, partnership with families and a therapeutic environment in order to minimize stress and pain. It is necessary to disseminate knowledge about the anomalies and their causes so that many causes are avoided, despite the genetic etiology being a contributing factor for a considerable percentage of congenital anomalies, avoidable factors such as infections that can be taken into account be transmitted to the fetus and maternal endocrinopathies.